Eradicate Village Fund Corruption: Efforts to Strengthen Law Enforcement - Hardyansah, Rommy; Farid, Mohamad; Atmari, Atmari; Didit; Zakki, Muhammad (Metromedia, 2022)
Abuses of village funds harm state finances, public security, and democratic values. In the management of village funds, there is still a discrepancy between the rules and practices. KPK found problems in the management of village funds that need to be understood because they have the potential to deviate. This study aims to determine law enforcement against perpetrators of misuse of village funds in Sidoarjo Regency. Data were collected through literature research on primary, secondary, and tertiary legal materials. In this study, several modes of corruption in the village were found, such as budget inflation, fictitious project activities, fictitious reports, embezzlement, and budget misuse. To prevent corruption in the village, the effectiveness of law enforcement is needed, supported by three elements of the legal system: legal substance, legal structure, and legal culture.